Environmental Preferences for Transportation Cycling Among Older Adults: An Experiment with Manipulated Photographs. (June 2018) - Van Cauwenberg, Jelle; De Bourdeaudhuij, Ilse; Clarys, Peter; Bas de Geus,; Deforche, Benedicte
Abstract : Background: Given that functional capacity (including leg strength, balance and reaction speeds) decreases with age, older adults may have different needs when cycling for transport compared to younger age groups. However, only a few studies have examined the environmental factors related to older adults' cycling for transport. Studies on the relationships between environmental factors and physical activity often suffer from following limitations; absence of an accurate neighborhood definition, lack of environmental heterogeneity, environmental co-variation, recall bias and lack of experimental designs. The use of manipulated photographs may overcome these limitations. The current study aimed to examine the effects of manipulating micro-scale environmental factors in a photographed street on the street's appeal for older adults' transportation cycling. Methods: Data were collected among 1248 Flemish older adults through an online or interview version of the questionnaire. This questionnaire included a choice-based conjoint exercise with manipulated photographs of a street. These manipulated photographs originated from one panoramic photograph of an existing street that was manipulated on seven environmental attributes. A sentence below each photograph indicated how long it would take the participant to reach his/her destination when choosing to cycle along this street (varying from 10 to 15 minutes). Participants chose which of two presented streets they would prefer to cycle for transport. Results: Type of cycle path (reflecting separation from motorized traffic and pedestrians) had the greatest effect on a street's appeal for transportation cycling (importance= 41.2%, 95% CI= 40.4–42.0). Participants had a clear preference for a cycle path that was separated from motorized traffic and pedestrians. The second most important factor was motorized traffic volume (importance= 16.4%, 95% CI= 15.8–17.0) with participants preferring streets with little traffic. This was followed by cycle path evenness (importance= 10.7%, 95% CI= 10.5–11.0) and distance (importance= 10.1%, 95% CI= 9.7–10.4). The remaining factors (speed limit, overall maintenance of the street, vegetation and the presence of a speed bump) appeared to be less important for older adults' transportation cycling. Conclusions: To promote transportation cycling among older adults through environmental modifications, the provision of cycle paths separated from motorized traffic and pedestrians should be prioritized.